A Novel Aquaporin Subfamily Imports Oxygen and Contributes to Pneumococcal Virulence by Controlling the Production and Release of Virulence Factors - Qingqing Hu (American Society for Microbiology, 2021)
ABSTRACT Aquaporins, integral membrane proteins widely distributed in organisms, facilitate the transport of water, glycerol, and other small uncharged solutes across cellular membranes and play important physiological roles in eukaryotes. However, characterizations and physiological functions of the prokaryotic aquaporins remain largely unknown. Here, we report that Streptococcus pneumoniae (pneumococcus) AqpC (Pn-AqpC), representing a new aquaporin subfamily possessing a distinct substrate-selective channel, functions as an oxygen porin by facilitating oxygen movement across the cell membrane and contributes significantly to pneumococcal virulence. The use of a phosphorescent oxygen probe showed that Pn-AqpC facilitates oxygen permeation into pneumococcal and Pn-AqpC-expressing yeast cells. Reconstituting Pn-AqpC into liposomes prepared with pneumococcal and Escherichia coli cellular membranes further verified that Pn-AqpC transports O2 but not water or glycerol. Alanine substitution showed that Pro232 in the substrate channel is key for Pn-AqpC in O2 transport. The deletion of Pn-aqpC significantly reduced H2O2 production and resistance to H2O2 and NO of pneumococci, whereas low-H2O2 treatment helped the ΔPn-aqpC mutant resist higher levels of H2O2 and even NO, indicating that Pn-AqpC-facilitated O2 permeation contributes to pneumococcal resistance to H2O2 and NO. Remarkably, the lack of Pn-aqpC alleviated cell autolysis, thus reducing pneumolysin (Ply) release and decreasing the hemolysis of pneumococci. Accordingly, the ΔPn-aqpC mutant markedly reduced survival in macrophages, decreased damage to macrophages, and significantly reduced lethality in mice. Therefore, the oxygen porin Pn-AqpC, through modulating H2O2 production and pneumolysin release, the two major pneumococcal virulence factors, controls the virulence of pneumococcus. Pn-AqpC orthologs are widely distributed in various pneumococcal serotypes, highlighting that the oxygen porin is important for pneumococcal pathogenicity. IMPORTANCE Pneumococcus is the leading cause of community-acquired pneumonia, bacteremia, and meningitis. This work reports that a novel aquaporin subfamily represented by pneumococcal Pn-AqpC functions as an oxygen porin facilitating O2 influx into cells. Importantly, by mediating O2 influx, Pn-AqpC controls the production and release of H2O2 and Ply, the two major pneumococcal virulence factors. Moreover, by enhancing endogenous H2O2 production, Pn-AqpC significantly increases pneumococcal resistance to H2O2 and even NO, the major bactericidal chemical produced by macrophages. Consequently, the deletion of Pn-aqpC markedly decreased pneumococcal survival in macrophages and reduced damage to macrophages. Accordingly, the ΔPn-aqpC mutant displays significantly attenuated virulence in a murine pneumonia model. Given that Pn-AqpC orthologs are widely distributed in all pneumococcal serotypes, this new subfamily of aquaporins is identified as novel virulence-related proteins.